How Valuable Could a Person Be?*. (15th July 2020) - Bailey, Andrew M.; Rasmussen, Joshua
Abstract: We investigate the value of persons. Our primary goal is to chart a path from equal and extreme value to infinite value. We advance two arguments. Each argument offers a reason to think that equal and extreme value are best accounted for if we are infinitely valuable. We then raise some difficult but fruitful questions about the possible grounds or sources of our infinite value, if we indeed have such value.